HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 43 MERANGIN - Doki Tamario; Ferinaldi; Hasmawati (Pendidikan Matematika | STKIP YM Bangko, 2021)
This research is a correlation study with a quantitative approach. The data collection techniques used in this study were questionnaire techniques and documentation methods. The population and sample in this study were students of Class VIII SMP Negeri 43 Merangin. The data analysis technique used is the Normality Test, Linearity, and Hypothesis Test. Based on the results of the analysis with the product moment correlation, it shows that there is a relationship between learning motivation and learning outcomes in Mathematics for class VIII grade SMP Negeri 43 Merangin. This is indicated by the magnitude of the r count value is greater than the r table (0.6430> 0.413) and a significance value of 0.000 which means less than 0.05 (0.000 <0.05), so this study succeeded in proving the hypothesis which states that